GABAergic Interneurons Shape the Functional Maturation of the Cortex - Le Magueresse, Corentin; Monyer, Hannah (Neuron, 2013)
From early embryonic development to adulthood, GABA release participates in the construction of the mammalian cerebral cortex. The maturation of GABAergic neurotransmission is a protracted process which takes place in discrete steps and results from the dynamic interaction between developmentally directed gene expression and brain activity. During the course of development, GABAergic interneurons contribute to key aspects of the functional maturation of the cortex in different ways, from exerting a trophic role to pacing immature neural networks. In this review, we provide an overview of the maturation of GABAergic neurotransmission and discuss the role of GABAergic interneurons in cortical wiring, plasticity, and network activity during pre- and postnatal development. We also discuss psychiatric diseases that may be considered at least in part developmental disorders of the GABAergic system.
Gesehen am 28.10.2021